High Frequency of Multiclass HCV Resistance-Associated Mutations in Patients Failing Direct-Acting Antivirals: Real-Life Data. Issue 3 (April 2019) - Gozlan, Yael; Bucris, Efrat; Shirazi, Rachel; Rakovsky, Avia; Ben-Ari, Ziv; Davidov, Yana; Veizman, Ella; Saadi, Tarek; Braun, Marius; Cohen-Naftaly, Michal; Shlomai, Amir; Shibolet, Oren; et al.
Background: Direct-acting antiviral (DAA) therapy has dramatically increased sustained virological response rates in HCV-infected patients. However, resistance-associated substitutions (RAS) interfering with NS3- and NS5A-targeted therapy, still emerge. This real-life study analysed the type and frequency of RAS in rare cases of patients failing DAA regimens in 12 clinical centres in Israel. Methods: Blood samples and clinical data from 49 patients who failed various DAAs were collected. RAS identified in the NS3 and NS5A regions by population (Sanger) and next-generation sequencing (NGS) were compared by treatment regimen and HCV subtypes. Results: The majority (71.4%, 35/49) of patients were infected with the genotype (GT)1b strain, while 12.2% (6/49) carried GT1a and 14.3% GT3a/b (7), GT4a (1) and GT1b/GT3a. RAS were identified in 85.7% (42/49) of failures, of which 90.5% (38/42) were clinically relevant RAS (known to be associated with a specific GT and DAA in patients failing therapy or those with more than twofold change in in vitro replicon assays). The most abundant RAS were 168A/E/Q/G/N/V (32.6%, 16/49) identified in NS3, and 93H/N (61.2%, 30/49), 31I/M/V (34.7%, 17/49) and 30R/H/K (12.2%, 6/49), identified in NS5A. Significantly more clinically relevant RAS were identified in NS5A (82.2%, 37/45) than in NS3 (35.7%, 10/28; P <0.01). While RAS were identified in all GT1a, GT3b and GT4a failures (100%, 10/10), only 71.8% (28/39) of GT1b or GT3a failures had RAS ( P =0.09). In four cases, NGS identified additional clinically relevant RAS and in one patient, NGS deciphered coexistence of GT3a and GT1b infections. Conclusions: Our findings, together with additional real-life data, will contribute to the optimization of retreatment in DAA failure, when cost-related and suboptimal regimens must be employed.